Quantification of Moss-Associated Cyanobacteria Using Phycocyanin Pigment Extraction - Renaudin, Marie; Darnajoux, Romain; Bellenger, Jean-Philippe (Frontiers in Microbiology, 2021)
In the boreal forest, cyanobacteria can establish associations with feather moss and realize the biological nitrogen fixation (BNF) reaction, consisting in the reduction of atmospheric dinitrogen into bioavailable ammonium. In this ecosystem, moss-associated cyanobacteria are the main contributors to BNF by contributing up to 50 % of new N input. Current environmental changes driven by anthropogenic activities will likely affect cyanobacteria activity (i.e., BNF) and populations inhabiting mosses, leading to potential important consequences for the boreal forest. Several methods are available to efficiently measure BNF activity, but quantifying cyanobacteria biomass associated with moss is challenging because of the difficulty to separate bacteria colonies from the host plant. Attempts to separate cyanobacteria by shaking or sonicating in water were showed to be poorly efficient and repeatable. The techniques commonly used, microscopic counting and qPCR, are laborious and time-consuming. In aquatic and marine ecosystems, phycocyanin, a photosynthesis pigment produced by cyanobacteria, is commonly used to monitor cyanobacteria biomass. In this study, we tested if phycocyanin extraction and quantification can be used to estimate cyanobacteria biomass inhabiting moss. We report that phycocyanin can be easily extracted from moss by freeze/thaw disturbance of cyanobacteria cells and can be quickly and efficiently measured by spectrofluorometry. We also report that phycocyanin extraction is efficient (high recovery), repeatable (RSD < 13 %) and that no significant matrix effects were observed. We conclude that phycocyanin extraction and quantification is an easy, rapid and efficient tool to quantify moss-associated cyanobacteria biomass.